2018
DOI: 10.1017/jgc.2018.1
|View full text |Cite
|
Sign up to set email alerts
|

A Problem-Oriented Group Approach to Reduce Children's Fears and Concerns About the Secondary School Transition

Abstract: To facilitate students’ transition into secondary school, a short, problem-oriented group program was designed that included interpretation retraining, problem solving, and social-skills training. Pre- and post-test data from two groups conducted over the course of 5 weeks were combined for a total of 35 6th-grade students waiting to undergo school transition. There was also a no-intervention control group (n = 19). Results indicate that completion of the program by the intervention group led to a significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…Finally, female participants with higher initial social anxiety symptoms appear to benefit the most from the intervention. Overall, these results not only extend the findings reported by Vassilopoulos et al (), but also add to previous evidence suggesting that participation in a coping skills training can have positive effects on children's emotional well‐being (Modecki et al, ). The results also support the effectiveness of the implementation of coping‐oriented interventions in various cultural settings.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Finally, female participants with higher initial social anxiety symptoms appear to benefit the most from the intervention. Overall, these results not only extend the findings reported by Vassilopoulos et al (), but also add to previous evidence suggesting that participation in a coping skills training can have positive effects on children's emotional well‐being (Modecki et al, ). The results also support the effectiveness of the implementation of coping‐oriented interventions in various cultural settings.…”
Section: Discussionsupporting
confidence: 89%
“…The group program was an adaptation of the intervention developed by Vassilopoulos and colleagues, which was found to be effective in reducing children's fears and concerns about the secondary school transition (see Vassilopoulos et al, ). The objectives of the coping‐oriented group program are twofold.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, most research tends to focus on the practicalities of the transition and preparing children for the new ways of learning, and social changes [1]. This is despite research which has shown children's emotional well-being to be directly linked to their academic and social functioning [12]. As a result, this has created a partial picture of the support children may need to manage this period which neglects their emotional needs.…”
Section: Introductionmentioning
confidence: 99%
“…Short-and long-term repercussions can include poor school adjustment and performance (Coelho & Romão, 2016), a decrease in self-esteem (Evans et al, 2018), a general sense of well-being (Copeland et al, 2013;Eskelä-Haapanen et al, 2017) and can ultimately result in mental health problems (Copeland et al, 2013). Failure to cope does not only affect the immediate school life but can lead to long-lasting negative consequences into adulthood (e.g., Evans et al, 2018;Lester et al, 2019;Vassilopoulos et al, 2018). However, if these challenges are overcome in a positive and constructive way, it can represent an opportunity for growth (Mowat, 2019).…”
Section: Introductionmentioning
confidence: 99%